PROFIL KETERCAPAIAN LAYANAN GURU BIMBINGAN DAN KONSELING - Ela Nurlaila; Endang Sri Budi Herawati (Jurnal Eksplorasi Bimbingan dan Konseling, 2019)
Guidance and Counseling Services is a process of providing assistance provided to students continuously in order to achieve independence in self-understanding. Guidance and Counseling Services are an integral part of education in an effort to help students to achieve optimal development, in accordance with their potential. But the fact is, not all services are carried out by BK teachers. This study aims to find out and understand the achievement of Guidance and Counseling Services at SMP N 1 Plered Cirebon District. This research is a qualitative research with case study method. The results showed that the BK teacher only did two of the nine services that should be carried out, namely counseling services for groups and individuals on students who were problematic. This condition is caused by the ratio of the number of students who are not in accordance with the number of BK teachers, so the service is not optimal.